Infantile lepromatous leprosy with vulvar localization - Bodamyali, Pertevniyal; Akay, Bengü Nisa; Kundakçi, Nihal; Erdem, Cengizhan; Okçu-Heper, Aylin; Akyol, Aynur (The Turkish Journal of Pediatrics, 2011)
Reports of leprosy during the first year of life are uncommon. In the early diagnosis, the spectrum for most of the children is reported to be largely confined to tuberculoid (TT), borderline tuberculoid (BT), mid-borderline (BB), and indeterminate forms of leprosy. We report a one-year-old female infant presenting numerous erythematous papules on her labium majus and pale flat macules on her chin and right cheek for about four months. A biopsy revealed changes typical for lepromatous leprosy (LL). Infantile leprosy and the route of transmission are discussed here.